Application of Cinnamon Bark Boiling to Reduce Blood Sugar Levels in Patients Type 2 Diabetes Mellitus - Dewi Mardiawati; Tri Putri Wahyuni; Satrio Bhagas Yudhanto (Sustainable Applied Modification Evidence Community (SAMEC), 2024)
Type II Diabetes Mellitus is a chronic disease characterized by an increase in blood sugar levels at times equal to or more than 200 mg/dL, and fasting blood sugar levels above or equal to 126 mg/dl. Diabetes Mellitus as a non-communicable disease is the number one cause of death in the world. It is estimated that 422 million adults lived with diabetes mellitus in 2014. Based on the 2018 Riskesdas results, the prevalence of type 2 DM based on doctor's diagnosis in Indonesia was 2.0%, whereas in 2013 it was only 1.5%. The aim of this research is the application of cinnamon bark decoction to reduce blood sugar levels in diabetes mellitus sufferers.This research was conducted in the working area of ​​the Lubuk Basung Community Health Center with a Quasi-Experimental research type with the research design being a one group pretest-posttest design. This research was conducted for 3 days on all clients suffering from Diabetes Mellitus who met the inclusion criteria.The research results showed that the average pretest blood sugar with cinnamon bark decoction in respondents was 215.88 mg/dL. The posttest blood sugar results for respondents with cinnamon bark were 163.38 mg/dL.The difference in reducing blood sugar levels in respondents with cinnamon bark was 52.5 mg/dl.So it can be concluded that there is an influence on sugar levels in diabetes mellitus patients by giving cinnamon decoction.